Individual and combined effects of dietary vitamin intake on cognitive function in elderly adults: the potential mediating role of serum neurofilament light chain levels - Zhikui Zhou; Baiyun Fan; Qiang Chen; Xuezhong Li; Xianjin Ke (Frontiers in Nutrition)
BackgroundVitamins are essential micronutrients for the prevention and treatment of neurodegenerative diseases. The objectives of the present study were to evaluate the association between dietary vitamin intake and cognitive function in elderly adults and to explore the potential impact of serum neurofilament light chain (NfL) concentration.MethodsData from 468 elderly individuals, including information on the dietary consumption of 10 vitamins, were used. Cognitive performance was assessed according to a composite Z-score of the Animal Fluency Test (AFT), Consortium to Establish a Registry for Alzheimer’s Disease (CERAD), and Digit Symbol Substitution Test (DSST). Serum NfL levels were measured using a highly sensitive immunoassay. Bayesian kernel machine regression (BKMR) models were used to estimate the combined effects of vitamin mixtures on cognitive function.ResultsIn both single- and multiple-vitamin models, individuals with a higher intake of dietary vitamin K exhibited greater global cognitive function, compared to those with a lower vitamin intake. BKMR revealed positive associations between vitamin mixtures and global cognitive function, AFT Z-scores, and DSST Z-scores. Individuals in the third vitamin K intake tertile exhibited lower serum NfL levels than those in the first tertile (regression coefficient, β = −0.16 [95% confidence interval −0.29 to −0.02]; p = 0.023). Serum NfL levels mediated the association between higher vitamin K intake and global cognitive function (8.73%).ConclusionVitamin mixtures were positively associated with global cognitive function in elderly participants. The association between vitamin K intake and cognitive function may be mediated by serum NfL concentration.